Characterization of Magnetic Metal Encapsulated in Multi-Walled Carbon Nanotubes Synthesized from Methyl Ester of Pongamia pinnata Oil and Its Application for Removal of Arsenic Ions from Aqueous Solution - Mahalingam, P.; Sivakumar, N.; Karthik, M.; Karthikeyan, S. (Asian Journal of Chemistry, 2014)
Magnetic metals Fe-Co encapsulated in multi-walled carbon nanotubes, were prepared by spray pyrolysis of methyl ester of Pongamia pinnata oil, a renewable carbon precursor, over Fe-Co catalyst supported on silica. Carbon nanostructures with different morphologies were obtained over Fe-Co catalyst supported on silica, with 20 mL/h feed rate of precursor at different temperatures (550, 650 and 750 °C). The products were characterized by scanning electron microscopy, transmission electron microscopy, Raman spectroscopy, thermogravimetry and vibrating sample magnetometer. The Fe-Co encapsulated in multi-walled carbon nanotubes was used as adsorbent for removal of As(V) ions from aqueous solution. Sorption experiments were conducted using batch system. The effect of pH on As(V) ions adsorption on the adsorbent, effect of initial As(V) ions concentration on adsorption by adsorbent and effect of temperature on As(V) ions removal were studied. The kinetics of As(V) ions adsorption on Fe-Co encapsulated in multi-walled carbon nanotubes was discussed.